(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2013)
New and detailed taphonomic and stratigraphical analyses have been carried out at the early Late Pleistocene site of “La Grave”, nearby Avetrana (Taranto, Southern Italy). These, together with population analyses of the principal species represented (Bos primigenius, Dama dama, Cervus elaphus, Sus scrofa and Stephanorhinus hemitoechus), suggest that the fossiliferous deposits were probably accumulated rapidly, over a short time span, by exceptional events of heavy rainfall with overbank flooding. These results are supported particularly by comparison of the mammalian death assemblages from Avetrana with data from recent and Pleistocene catastrophic death assemblages documented in the literature. Furthermore, population analysis of species pinpoints the time of death between late autumn and winter. Periods with abundant and heavy rainfall are recorded in Late Pleistocene Mediterranean marine cores by the presence of sapropel levels, and in continental pollen diagrams covering the same time. Finally, observations on the morphometric variations in the bones of Bos primigenius reveal an increase in size of the species during the early Late Pleistocene and a decrease in size during the late Late Pleistocene and the Holocene. SHORT NOTE-NOTA BREVE